Source and depositional processes of coarse-grained limestone event beds in Frasnian slope deposits (Kostomłoty-Mogiłki quarry, Holy Cross Mountains, Poland) - Vierek, Aleksandra (Geologos, 2010)
The Kostomłoty-Mogiłki succession is situated in the Kostomłoty transitional zone between the shallow-water Kielce stromatoporoid-coral platform and the deeper Łysogóry basin. In the Kostomłoty-Mogiłki quarry, the upper part of the Szydłówek Beds and Kostomłoty Beds are exposed. The Middle-Upper Frasnian Kostomłoty Beds are composed of shales, micritic and nodular limestones with abundant intercalations of detrital limestones. The dark shales and the micritic and nodular limestones record background sedimentation. The interbedded laminated and detrital limestones reflect high-energy deposition (= event beds). These event beds comprise laminated calcisiltites, fine-grained calcarenites, coarse-grained grain-supported calcirudites fabrics, and matrix-supported calcirudites. The material of these event beds was supplied by both erosion of the carbonate-platform margin and cannibalistic erosion of penecontemporaneous detrital limestones building the slope of this platform. Storms and the tectonic activity were likely the main causes of erosion. Combined and gravity flows were the transporting mechanisms involved in the reworking and redeposition.